An Economic Basis for the "National Defense Argument" for Aiding Certain Industries - Thompson, Earl A. (Journal of Political Economy, 1979)
Two alternative theories, each generating a "national defense argument" for protectionism, are developed and tested. The theory surviving the tests states that wartime price controls imply an undervaluation of peacetime stocks of capital which produce the war-controlled outputs. Optimal policy responses to these undervaluations are derived. For example: Nonimported, undervalued capital goods should receive domestic subsidies; undervalued capital goods, imported in peacetime but not in wartime, should receive import protection; and undervalued capital goods which are imported in wartime should be granted cartel status. An application to the United States indicates that the theoretical optimum is approximated by observed policy.